Improving Critical Thinking Skills of Elementary School Students: Project Based Learning vs Gamification-Based Group Investigation - Koten, Gaudensius Jati Lamauran; Munzil; Utama, Candra (Universitas Pendidikan Ganesha, 2023)
Indonesia's educational achievements in the international arena are still classified as less than optimal. Learning in schools in general, which has not abandoned conventional learning, is one of the causes. It is very important to present innovation in Indonesian education, especially in the learning process in schools, with various creative approaches, such as implementing integration between learning models and approaches. The purpose of this study was to compare the critical thinking skills of students who received learning using the gamification-based PjBL model with those of students who received learning using the gamification-based GI model. This type of research is experimental research, namely a quasi-experimental research design with a non-equivalent control group design. The subjects in this study consisted of fifth grade students at two different public elementary schools with a total of 25 and 26 students respectively. Data collection was carried out through pretest and posttest activities using a questionnaire of 20 questions. The collected data were analyzed using the Independent Sample T-Test and the N-Gain test. The results of data analysis show that the percentage of effectiveness of the gamification-based PjBL model is greater than the percentage of effectiveness of the gamification-based GI model (56.2890 > 53.4372). These results indicate that the gamification-based PjBL model is more effective at improving students' critical thinking skills compared to the gamification-based GI model. It's just that the difference does not appear to be significant.